Hydrogen Peroxide Is an Endothelium-Derived Hyperpolarizing Factor in Animals and Humans - Matoba Tetsuya; Hiroaki Shimokawa (Elsevier, 2003)
Vascular endothelium plays an important role in maintaining vascular homeostasis by synthesizing and releasing several vasodilating factors, such as prostacyclin, nitric oxide (NO), and a yet unidentified endothelium-derived hyperpolarizing factor (EDHF). Possible candidates for EDHF include epoxyeicosatrienoic acids, endothelium-derived K+ ions, and as we have recently identified, hydrogen peroxide (H2O2). Electrical communication between endothelial and smooth muscle cells through gap junctions has also been suggested to be involved in endothelium-dependent hyperpolarization. Among the above candidates, the H2O2 hypothesis well explains the pathophysiological interactions between NO and EDHF and re-highlights the physiological roles of the reactive oxygen species in endothelium-dependent vascular responses. This brief review summarizes our current knowledge about H2O2 as an EDHF, with special reference to its production by the endothelium, its action on membrane potentials and its pathophysiological roles.